Tingkat Pelayanan Angkutan Perintis di Daerah Terisolir - Romadhona, Prima Juanita (Warta Penelitian Perhubungan, 2011)
Indonesia is an archipelago country which causing unequal development distribution in some areas. As one of the gauernment's efforts towards equitable development, they built pioneer transportation in remote areas that is expected to increase the local economy level. Based quantitative analysis, the aim of this study is to find out the services of pioneer transportation in remote areas. On of pioneer transportation route services is at East Nusa Tenggara Prauince which through 4 pools namely Kefamenanu Pool, Pool Ende, Waingapu Pool, and Pool Kupang. Routes that cross these pools have load factor between 30-40%. In addition, comparison of the level of fleet operation and high availability on all routes pioneer in East Nusa Tenggara Prauince reached 100%. This means all existing vehicles to operate to serve the routes pioneers. Nevertheless, there are several routes that have a high level of service that is Kefamenanu - Motadik, Kefamenanu -Wini - Ponu, Kefamenanu - Oekolo, Kupang - Kuanfatu, Kupang - Kolbano, and Kupang - Naikliu. Based on the respondents perception, more than 90% said that pioneer transportation is needed in order to open mobility for remote areas. Moreauer, also concluded that the tariff of pioneer transport that expects the prauision is affordable then need additional fleet quality that fix in the pioneer route.Keywords: remote areas, pioneer transportation